(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Rabindranath Tagore is a standout amongst the most shining Stars in Indian English writing and might be along these lines, while presenting him Kh. Kunjo Singh says, ’to acquaint Rabindranath Tagore resembles with present an age’. Till today following hundred years as his death, regardless he remained as the most unmistakable and understood figure in Indian writing in English just as in English writing. Rabindranath Tagore’s estimation of Indian nationalism is best communicated by the term ’ambivalence’. Incomprehensibly, he had made the national anthems for three nations India, Bangladesh and Sri Lanka. This ambivalent reaction of Tagore towards nationalism as an ideology was evident in the entangled arrangement of reactions he got from Indians and non-Indians alike. For the British, he was the quintessential agent of the secretive Orient. His English writings, in certain political settings, reverberated profoundly inside the Anglophone world. However, the British intellectual elite felt uneasy with his ’extraordinary’ persona. At home, Tagore built up the idea of ’syncretic’ human advancement as a premise of nationalist civilizational solidarity, where ’samaja’ (society) was given centrality, in contrast to the European model of state-driven development. The virtuoso of Tagore had viably predicted this dilemma, thinking back to the 1890s. In his words, Her [India’s] issue was the issue of the world in smaller than usual. India is excessively tremendous in its territory and excessively various in its races. It is numerous nations stuffed in one land container. Tagore comprehended the risks that the improvement of nationalism in such a quandary presented to what he called the Indian samaj. Post 1917, after the distribution of his book Nationalism, Tagore rose as a scrutinization of the cutting edge nation-state. So were Romain Ronnald from France and Albert Einstein from Germany. In this article, we studied the sense of Nationalism in Rabindranath Tagore’s works.